2003
DOI: 10.1016/s0273-1177(03)00294-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of stellar coronae with XMM-Newton

Abstract: The XMM-Newton observatory has given a strong new impetus to the investigations of stellar coronae. It carries high-resolution X-ray spectroscopic instruments that give access to information on the physical conditions in coronal plasmas. Furthermore, its imaging detectors produce high-quality X-ray light curves and images with a large field of view. I review results on stellar coronae obtained with XMM-Newton between its launch in late 1999 and the present (late 2002). Among other topics, I discuss the element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Since we see in this study good evidence for a trend of decreasing Mg XI R ratio with increasing L X /L bol , the correlation of Ne X/Mg XI line strength with Mg XI R ratio would be expected if the Ne/Mg abundance ratio increased with L X /L bol . While the Ne/Mg abundance ratio remains to be investigated thoroughly in the stars of our sample, the evidence from analyses to date summarised by Drake (2003) and Audard (2003) does suggest that the relative Ne enhancement increases with stellar activity.…”
Section: Density Correlated With Ne/mg?mentioning
confidence: 82%
“…Since we see in this study good evidence for a trend of decreasing Mg XI R ratio with increasing L X /L bol , the correlation of Ne X/Mg XI line strength with Mg XI R ratio would be expected if the Ne/Mg abundance ratio increased with L X /L bol . While the Ne/Mg abundance ratio remains to be investigated thoroughly in the stars of our sample, the evidence from analyses to date summarised by Drake (2003) and Audard (2003) does suggest that the relative Ne enhancement increases with stellar activity.…”
Section: Density Correlated With Ne/mg?mentioning
confidence: 82%
“…Emission lines have been recorded by several solar missions, such as Skylab (Dere 1978). In the recent years, high-resolution XUV spectroscopic observations by Chandra and XMM-Newton satellites, have also shown that a vast number of astrophysical sources produce emission lines from Be-like ions, such as Fe XXIII (Audard 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their importance to astrophysics, extensive IC R-matrix calculations for Be-like iron and nickel were carried out by Chidichimo et al (2005;2003) within the Iron Project, following an early distorted wave study by Bhatia & Mason (1981). In Chidichimo et al (2005), collision strengths and effective collision strength were obtained for Be-like Fe for the configurations n = 2, 3, 4, including a total of 98 fine-structure levels in the basis set.…”
Section: Introductionmentioning
confidence: 99%
“…They are ideal targets for X-ray spectroscopy since they display a wealth of bright emission lines of various elements. Recent reviews summarize results obtained in the first years after the launch of Chandra and XMM-Newton (e.g., Audard 2003, Linsky 2003. In particular, patterns in coronal abundances have been recognized in which elements with a first ionization potential (FIP) < 10 eV are underabundant with respect to the high-FIP elements when observed in very active stars; this is opposite to the solar FIP effect in which low-FIP elements are overabundant whereas high-FIP elements are of photospheric composition.…”
Section: Introductionmentioning
confidence: 99%